Peningkatan Keterampilan Menulis Karangan Narasi Berbahasa Jawa melalui Penerapan Metode Mind Mapping dan Penggunaan Media Gambar Berseri Berbasis IT pada Siswa Kelas VII E SMP N 1 Banyudono - Mardian Dewi Pamungkas; Raheni Suhita; Djoko Sulaksono (Sabdasastra : Jurnal Pendidikan Bahasa Jawa, 2022)
This research aims to increase: (1) the quality of learning process seen from student learning motivation aspect in writing javanese narrative essay; and (2) the students’ skill in writing javanese narrative essay on VII E Grade SMP N 1 Banyudono through applying mind mapping method and using serial picture IT based. This research is a classroom action research which conducted in two cycles, with each cycle consisting of two meetings. The subjects were students of VII E Grade SMP N 1 Banyudono, the total of the students is 32 students. The data sources are informants (teacher and student), events, and documents. The datas were collected by interview, observation, test, and document analysis. The validity of the data using data triangulation and method triangulation. Data were analyzed using descriptive tehniques comparative and critical analysis. Based on the result of this research concluded that applying mind mapping method and using serial picture IT based can improve: (1) the quality of process in writing javanese narrative essay learning that seen from students’ learning motivation aspect; and (2) the result of students’ learning in writing javanese narrative essay in each cycle. The increase can be done with the procedures of learning as follows: (1) students are given a theme to create a narrative essay by displaying a themed serial picture; (2) students make mind mapping central in the midst of a picture of the mind mapping center; (3) students make the main branch emanating directly from mind mapping central; (4) students write the keyword above the branch, long branches adapted to long word; (5) students added a picture that is accordance with keywords in the mind mapping sheet; and (6) students develop a narrative essay based on mind mapping became a essay that is complete.